2019
DOI: 10.1093/jas/skz264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brewer’s spent grain and carrot pomace on digestibility, fecal microbiota, and fecal and urinary metabolites in dogs fed low- or high-protein diets1

Abstract: Brewer’s spent grain (BSG) and carrot pomace (CAP) were used as fiber sources in low- or high-protein diets in dogs. Ten adult Beagles were involved in 5 feeding periods of 19 d in a cross-over design. Experimental diets contained 7.5% of total dietary fiber (TDF) from BSG or CAP and 20% or 40% of crude protein in dry matter. A diet with 3.5% TDF from both fiber sources and 20% crude protein was used as reference. Fecal dry matter was 27% higher for diets with BSG compared to CAP (P < 0.001). Apparent fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The intervention diet in this study consisted of many nutrients and dietary components that may have an influence on both health and GM composition, including water ( Cameron et al, 2011 ; Deng et al, 2014 ; Alexander, Colyer & Morris, 2014 ), prebiotic fibers ( Middelbos et al, 2010 ; Panasevich et al, 2015 ; Alexander et al, 2018 ; Eisenhauer et al, 2019 ), omega-3 fatty acids ( Bauer, 2011 ), carotenoids, and polyphenols ( Kolchin et al, 1991 ; Kim et al, 2000 ; Chew et al, 2000 ; Massimino et al, 2003 ; Hall et al, 2006 ; Carrera-Quintanar et al, 2018 ; Lyu et al, 2018 ), although high-quality extruded diets may include these nutrients and compounds as well. Nutrient and energy digestibility has also been observed to be different between extruded kibble and MC diets ( Algya et al, 2018 ), and it may facilitate differential impacts on health and GM.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention diet in this study consisted of many nutrients and dietary components that may have an influence on both health and GM composition, including water ( Cameron et al, 2011 ; Deng et al, 2014 ; Alexander, Colyer & Morris, 2014 ), prebiotic fibers ( Middelbos et al, 2010 ; Panasevich et al, 2015 ; Alexander et al, 2018 ; Eisenhauer et al, 2019 ), omega-3 fatty acids ( Bauer, 2011 ), carotenoids, and polyphenols ( Kolchin et al, 1991 ; Kim et al, 2000 ; Chew et al, 2000 ; Massimino et al, 2003 ; Hall et al, 2006 ; Carrera-Quintanar et al, 2018 ; Lyu et al, 2018 ), although high-quality extruded diets may include these nutrients and compounds as well. Nutrient and energy digestibility has also been observed to be different between extruded kibble and MC diets ( Algya et al, 2018 ), and it may facilitate differential impacts on health and GM.…”
Section: Discussionmentioning
confidence: 99%
“…The indoles and phenols in the urine were measured by gas chromatography (GC 6890 N, Agilent Technologies), as described by Eisenhauer et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
“…For the detection of indoxyl sulphate in the urine of the dogs, the method described by Curzon and Walsh (1962) was used. The indoles and phenols in the urine were measured by gas chromatography (GC 6890 N, Agilent Technologies), as described by Eisenhauer et al (2019).…”
Section: Materials and Me Thodsmentioning
confidence: 99%
“…Data on the digestive parameters and fecal microbial composition of dogs have also suggested that BSG can be used as a source of fiber in the canine diet (Eisenhauer et al 2019). Also, recently, BSG was used as a substrate to rear different insects, such as the black soldier fly larva (Hermetia illucens) and mealworm larva (Tenebrio molitor) (Mancini et al 2019;Melis et al 2019;Shumo et al 2019).…”
Section: Brewers' Spent Grain In Human and Animal Dietsmentioning
confidence: 99%